Wave overtopping and toe scouring at a plain vertical seawall with shingle foreshore: A physical model study. (1st January 2019) - Salauddin, M.; Pearson, J.M.
Abstract: This paper describes a physical model study to investigate the wave overtopping and toe scouring at a plain vertical wall with a shingle foreshore. A matrix of 180 experimental test conditions were performed in a 2D wave flume, with an approximate scale of 1:50. The study investigates the baseline overtopping characteristics at a plain vertical wall on an impermeable 1:20 foreshore slope and compares the results with two permeable 1:20 shingle beach foreshores with prototype d50 values of 13 mm, and 24 mm respectively. For impulsive wave conditions, it was found that the mean overtopping rate was reduced by factor 3 for the d50 of 13 mm, and a factor of 4 for the d50 of 24 mm. For non-impulsive waves, the reduction factors were 1.5 for d50 of 13 mm and 2 for d50 of 24 mm. Prior to this study, limited design guidance was available to predict the mean overtopping discharges and mean sediment rates at vertical seawalls on permeable shingle foreshores. Therefore, a new set of prediction formulae are proposed in this study, based on the new laboratory test results, and a comparison with the available prediction methods in literature for vertical seawalls subjected to both impulsive and non-impulsive wave conditions. Highlights: The study investigates the baseline overtopping characteristics at a plain vertical wall on an impermeable 1:20 foreshore slope, and compares the results with two permeable 1:20 shingle beach foreshores with prototype d50 values of 13 mm, and 24 mm respectively. The resulting overtopping characteristics correspond to impermeable bed showed an overall good agreement with the available empirical prediction methods for both impulsive and non-impulsive wave conditions. For impulsive wave conditions tested within this study, it was observed that the mean overtopping rate is reduced by factor 3 and 4 for d50 of 13 mm and 24 mm respectively, when impermeable and shingle beaches are compared. For non-impulsive waves, the reduction factors were 1.5 for d50 of 13 mm and 2 for d50 of 24 mm. A new set of prediction formulae are proposed, to estimate the overtopping at vertical seawalls with shingle foreshores.